2021
DOI: 10.1111/petr.14178
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplant outcomes in children and adolescents with systemic lupus erythematosus

Abstract: Background: Literature supports equivalent kidney transplant outcomes in adults with systemic lupus erythematosus (SLE) compared with those without SLE. However, there are conflicting and scant data on kidney transplant outcomes, as well as controversy over optimal timing of transplantation, in children and adolescents with SLE. Methods: Analysis included kidney-only transplant recipients aged 2-21 years from 2000 to 2017 enrolled in the Organ Procurement and Transplant Network (OPTN). The relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It has been thought that allowing for disease remission and symptom quiescence via an extended waiting period would prevent post-transplantation complications and allograft loss [ 41 43 ]. This practice is a likely contributor to our finding however, evidence that this longer wait time provides any benefit has been mixed, with some studies showing an increased risk of graft failure [ 42 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…It has been thought that allowing for disease remission and symptom quiescence via an extended waiting period would prevent post-transplantation complications and allograft loss [ 41 43 ]. This practice is a likely contributor to our finding however, evidence that this longer wait time provides any benefit has been mixed, with some studies showing an increased risk of graft failure [ 42 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…In their study comparing 40 children with SLE to 1048 children with dysplasia/hypoplasia from the European Society of Paediatric Nephrology and European Renal Association and European Dialysis and Transplant Association (ESPN/ERA-EDTA) registry, Van Stralen et al [2] found a three-fold increased risk of graft loss in patients with lupus nephritis when adjusting for the lower rate of living donation and preemptive transplant. Mai et al [19 ▪▪ ] recently corroborated these results in their study comparing 457 children with SLE to 4492 children with non-SLE-related glomerular disease and 5605 children with nonglomerular disease in the Organ Procurement and Transplant Network/Scientific Registry of Transplant Recipients (OPTN/SRTR). Children with SLE had higher risk of allograft failure (hazard ratio 1.67, P = 0.001 and 1.42, P = 0.03, respectively) and mortality (hazard ratio 1.42, P < 0.001 and 1.24, P = 0.005, respectively) than both of the other two groups.…”
Section: Lupus Nephritismentioning
confidence: 75%
“…Unlike adults where allograft survival in SLE patients is similar to other causes of ESKD [9,10,18,19 ▪▪ ], allograft survival in pediatric patients with SLE appears to be significantly lower. In their study comparing 40 children with SLE to 1048 children with dysplasia/hypoplasia from the European Society of Paediatric Nephrology and European Renal Association and European Dialysis and Transplant Association (ESPN/ERA-EDTA) registry, Van Stralen et al [2] found a three-fold increased risk of graft loss in patients with lupus nephritis when adjusting for the lower rate of living donation and preemptive transplant.…”
Section: Lupus Nephritismentioning
confidence: 80%